Developing Modified Batting Media for Striking Skills in Physical Education - Armin Haluti; Abu Bakar (Journal of Pedagogy and Education Science, 2026)
The teaching of striking skills in senior high school physical education often faces challenges related to limited equipmeThe teaching of striking skills in senior high school physical education often faces challenges related to limited equipment, low student confidence, and difficulties in mastering correct batting mechanics. This study aimed to develop and evaluate modified batting instructional media for striking skill learning among Grade 10 physical education students. Employing a research and development design based on the ADDIE model, this study produced modified batting tools and instructional variations tailored to students’ physical characteristics and learning needs. The development process involved expert validation by three validators, consisting of two university lecturers with expertise in physical education pedagogy and instructional media development and one experienced physical education teacher, followed by field trials involving one intact Grade 10 physical education class at SMAN 3 Luwuk, Central Sulawesi, Indonesia (N = 32). The findings showed that the developed instructional media achieved high expert validity scores (≥85%) and were perceived by students as praThe teaching of striking skills in senior high school physical education often faces challenges related to limited equipment, low student confidence, and difficulties in mastering correct batting mechanics. This study aimed to develop and evaluate modified batting instructional media for striking skill learning among Grade 10 physical education students. Employing a research and development design based on the ADDIE model, this study produced modified batting tools and instructional variations tailored to students’ physical characteristics and learning needs. The development process involved expert validation by three validators, consisting of two university lecturers with expertise in physical education pedagogy and instructional media development and one experienced physical education teacher, followed by field trials involving one intact Grade 10 physical education class at SMAN 3 Luwuk, Central Sulawesi, Indonesia (N = 32). The findings showed that the developed instructional media achieved high expert validity scores (≥85%) and were perceived by students as praThe teaching of striking skills in senior high school physical education often faces challenges related to limited equipment, low student confidence, and difficulties in mastering correct batting mechanics. This study aimed to develop and evaluate modified batting instructional media for striking skill learning among Grade 10 physical education students. Employing a research and development design based on the ADDIE model, this study produced modified batting tools and instructional variations tailored to students’ physical characteristics and learning needs. The development process involved expert validation by three validators, consisting of two university lecturers with expertise in physical education pedagogy and instructional media development and one experienced physical education teacher, followed by field trials involving one intact Grade 10 physical education class at SMAN 3 Luwuk, Central Sulawesi, Indonesia (N = 32). The findings showed that the developed instructional media achieved high expert validity scores (≥85%) and were perceived by students as practical, engaging, and easy to use. Implementation results indicated improved student participation, confidence, and execution of fundamental striking movements during learning activities. These results suggest that modified batting instructional media can help address equipment limitations and learner variability while supporting more inclusive skill learning. In conclusion, the developed media are feasible for supporting striking skill learning in senior high school physical education.ctical, engaging, and easy to use. Implementation results indicated improved student participation, confidence, and execution of fundamental striking movements during learning activities. These results suggest that modified batting instructional media can help address equipment limitations and learner variability while supporting more inclusive skill learning. In conclusion, the developed media are feasible for supporting striking skill learning in senior high school physical education.ctical, engaging, and easy to use. Implementation results indicated improved student participation, confidence, and execution of fundamental striking movements during learning activities. These results suggest that modified batting instructional media can help address equipment limitations and learner variability while supporting more inclusive skill learning. In conclusion, the developed media are feasible for supporting striking skill learning in senior high school physical education.nt, low student confidence, and difficulties in mastering correct batting mechanics, which can hinder effective skill acquisition. This study aimed to develop and evaluate modified batting instructional media to enhance striking skill learning among Grade 10 physical education students. Employing a research and development design based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study produced a set of modified batting tools and instructional variations tailored to students’ physical characteristics and learning needs. The development process involved expert validation by specialists in physical education pedagogy, instructional media, and an experienced physical education teacher, followed by field trials to assess product practicality and attractiveness among Grade 10 students. The findings revealed that the developed instructional media achieved high validity scores from experts (≥85%) and were perceived by students as practical, engaging, and easy to use. Implementation results indicated increased student participation, improved confidence, and better execution of fundamental striking movements during learning activities. These results demonstrate that modified batting instructional media contribute meaningfully to addressing equipment limitations and learner variability in physical education settings while supporting more inclusive and effective skill learning. In conclusion, the developed media are feasible and effective for enhancing striking skills in senior high school physical education, and it is recommended that teachers adopt and further adapt similar modified instructional media to optimize skill-based learning and student engagement.